2020
DOI: 10.32938/jpm.v2i1.468
|View full text |Cite
|
Sign up to set email alerts
|

Eksplorasi Etnomatematika Acara Adat Thelas Keta Pada Masyarakat Noemuti

Abstract: Pada hakekatnya matematika merupakan ilmu pengetahuan yang digunakan untuk menyelesaikan masalah sehari – hari, sedangkan budaya merupakan pola hidup yang terdapat dalam masyarakat yang diwariskan secara turun – temurun. Keterkaitan antara matematika dan budaya dikenal dengan istilah etnomatematika. Etnomatematika merupakan matematika tumbuh dan berkembang dalam budaya. Dengan menerapkannya etnomatematika sebagai suatu pendekatan pembelajaran akan sangat memungkinkan siswa untuk lebih paham dengan materi yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Based on the results of observations, it was found that the shape of the flat shape (geometry) in this study is ethnomathematics as a form of exploring the concept of cultural mathematics in the traditional engklek game, namely in a grid pattern consisting of 3 etching shapes, namely plane maps, house plots and people plots which show a flat shape shape. Namely square, rectangle, square, circle, and trapezoid, the gaco used in the traditional engklekt game also contains two-dimensional geometry, namely triangles, circles, ellipses, trapezoids and rectangles, in line with research on ethnomathematics of other cultures in Indonesia, for example in several Rajapolah woven crafts contain mathematical elements, one of which is the use of the tessellation or tiling principle, geometric shapes that can tessellate for example squares, triangles, regular pentagons, regular hexagons and can also be curves [17], the Muaro Jambi Temple building consists on sus ancient brickwork in square and rectangular shapes on the walls of Gumpung Temple, the arrangement of bricks at the entrance to Gumpung and Umpak Batu Temples so that the mathematical concept in the form of geometry is also found in Muaro Jambi Temple [18], several parts of the grand mosque in Yogyakarta have aspects Mathematically, namely the carvings (ornaments), the pavilion, the roof of the mosque, the kentongan (drum), parts of the floor and the gate related to the concept of geometry including flat buildings and the spatial structure of the Great Mosque in Yogyakarta [19], traditional Biak-Papua cultural houses have a mathematical concept, namely the roof shape of rum som (rectangular and triangular shapes, sram mankubui roofs (trapezoidal and triangular), tifa (conical) [21], in the Thelas Keta traditional event for the noemuti community there are several mathematical concepts, namely circles, rhombuses, and rectangles [31], the shape of the house building is at Minangkabau there is a mathematical concept, namely in two-dimensional geometry (geometry), namely squares, rectangles, trapezoids, triangles, isosceles triangles, equilateral triangles, pentagons, circles and rhombuses [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of observations, it was found that the shape of the flat shape (geometry) in this study is ethnomathematics as a form of exploring the concept of cultural mathematics in the traditional engklek game, namely in a grid pattern consisting of 3 etching shapes, namely plane maps, house plots and people plots which show a flat shape shape. Namely square, rectangle, square, circle, and trapezoid, the gaco used in the traditional engklekt game also contains two-dimensional geometry, namely triangles, circles, ellipses, trapezoids and rectangles, in line with research on ethnomathematics of other cultures in Indonesia, for example in several Rajapolah woven crafts contain mathematical elements, one of which is the use of the tessellation or tiling principle, geometric shapes that can tessellate for example squares, triangles, regular pentagons, regular hexagons and can also be curves [17], the Muaro Jambi Temple building consists on sus ancient brickwork in square and rectangular shapes on the walls of Gumpung Temple, the arrangement of bricks at the entrance to Gumpung and Umpak Batu Temples so that the mathematical concept in the form of geometry is also found in Muaro Jambi Temple [18], several parts of the grand mosque in Yogyakarta have aspects Mathematically, namely the carvings (ornaments), the pavilion, the roof of the mosque, the kentongan (drum), parts of the floor and the gate related to the concept of geometry including flat buildings and the spatial structure of the Great Mosque in Yogyakarta [19], traditional Biak-Papua cultural houses have a mathematical concept, namely the roof shape of rum som (rectangular and triangular shapes, sram mankubui roofs (trapezoidal and triangular), tifa (conical) [21], in the Thelas Keta traditional event for the noemuti community there are several mathematical concepts, namely circles, rhombuses, and rectangles [31], the shape of the house building is at Minangkabau there is a mathematical concept, namely in two-dimensional geometry (geometry), namely squares, rectangles, trapezoids, triangles, isosceles triangles, equilateral triangles, pentagons, circles and rhombuses [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the development of research related to ethnomathematics has begun to increase; this can be seen from the various types of research conducted from multiple cultures in Indonesia. The studies conducted examining ethnomathematics in mathematical concepts are the Panjalin Traditional House [16], Rajapolah Woven Craftsmen Tasikmalaya Regency [17], Muaro Jambi Temple [18], the Great Mosque in Yogyakarta [19], elements of Javanese culture [7], Ancient wells of Kaliwadas Village Cirebon [20], Houses and Traditional Musical Instruments of Biak-Papua Culture [21], Tradition of Measurement of the Sasak Tribe Community [22,23], Indigenous People (SAD) Batanghari Regency, Jambi Province [24], adipurwo batik [25] Teak Joglo House [26], Fort Marlborough [27], Yogyakarta Batik [28], Cassava Leaf Painting Batik at the Daweea Batik Production House [29], the Empat Lawang Turbid Air Pasemah Tribe [30], Thelas Keta traditional events for the noemuti community [31], Minangkabau Gadang House, West Sumatra [32,33]. This is influenced by the many and varied cultures in Indonesia, from Sabang to Merauke, thus attracting the interest of researchers and teachers to study ethnomathematics in various cultures in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang tersedia hanya terkait "Eksplorasi Etnomatematika pada Tradisi Malam Tujuh Likur Masyarakat Daik Kepulauan Riau" oleh Taur dkk yang menemukan unsur-unsur matematika berupa konsep barisan aritmatika, konsep bilangan, geometri, luas daerah, volume benda putar dan konsep transformasi (refleksi/pencerminan) (Taur et al, 2020). Selanjutnya terdapat juga penelitian serupa yang berjudul "Eksplorasi Etnomatematika Acara Adat Thelas Keta pada Masyarakat Noemuti" oleh Kou dkk yang menemukan konsep-konsep matematika yaitu garis, bangun datar persegi panjang, bangun datar lingkaran, dan konsep bangun datar belah ketupat pada alat dan bahan yang digunakan dalam acara adat Thelas Keta (Kou & Deda, 2020). Kemudian terdapat juga penelitian dari Yudanti dkk dengan judul "Eksplorasi Etnomatematika Terkait Aktivitas Fundamental pada Rumoh Aceh".…”
unclassified